New Lepidium (Brassicaceae) from New Zealand - de Lange, P. J. (Pensoft Publishers, 2013)
Abstract. A revision of the New Zealand endemic Lepidium oleraceum and allied species is presented. Sixteen species are recognised, 10 of these are new. The new species are segregated on the basis of morphological characters supported by molecular data obtained from three DNA markers (two rDNA and one cpDNA). One species, Lepidium castellanum sp. nov., is endemic to the Kermadec Islands where it is sympatric with Lepidium oleraceum. The North Island of New Zealand supports four species, with two of them, Lepidium amissum sp. nov. and Lepidium obtusatum, now extinct. The South Island supports six species, that, aside from Lepidium banksii, Lepidium flexicaule and Lepidium oleraceum, are all confined to the south-eastern half of the island (Lepidium aegrum sp. nov., Lepidium crassum sp. nov. and Lepidium juvencum sp. nov.). One of these, Lepidium juvencum sp. nov., extends to Stewart Island. The Chatham Islands support six species (Lepidium flexicaule, Lepidium oblitum sp. nov., Lepidium oleraceum, Lepidium oligodontum sp. nov., Lepidium panniforme sp. nov., and Lepidium rekohuense sp. nov.), one of which, Lepidium oligodontum sp. nov., extends to the Antipodes Islands group. The remote, subantarctic Bounty Islands group supports one endemic, Lepidium seditiosum sp. nov., which is the only vascular plant to be recorded from there. Lepidium limenophylax sp. nov. is known from islands off the south-western side of Stewart Island/Rakiura, The Snares and Auckland islands. Lepidium naufragorum, although not related to Lepidium oleraceum and its allies, is also treated because populations with entire leaves are now known. Typification is undertaken for Lepidium banksii, Lepidium oleraceum, Lepidium oleraceum var. acutidentatum, var. frondosum and var. serrulatum.